2012
DOI: 10.1074/jbc.m112.344994
|View full text |Cite
|
Sign up to set email alerts
|

A2B Adenosine Receptor Promotes Mesenchymal Stem Cell Differentiation to Osteoblasts and Bone Formation in Vivo

Abstract: Background:The A2BAR signals via cAMP. Cyclic AMP signaling has been shown to regulate MSC differentiation. Results: A2BAR KO mice have reduced differentiation of osteoblasts, a mild osteopenic phenotype, and impaired fracture physiology. A2BAR activation increases the differentiation of osteoblasts. Conclusion: The A2BAR regulates bone homeostasis. Significance: A2BAR signaling is a component of bone homeostasis, particularly after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(154 citation statements)
references
References 54 publications
(59 reference statements)
14
138
1
Order By: Relevance
“…The work presented here showed no effects of adenosine, 2-chloroadenosine, GR79236 or BAY606583 on calvarialderived osteoblasts; this is in broad agreement with previous studies which showed exogenous adenosine had no effect on cultured rat osteoblasts [11,29]. However, our results are at variance with several studies which found that adenosine or adenosine analogues, acting via the A 2A or A 2B receptors, stimulate the differentiation and function of human and rodent bone marrow osteoblasts and promote bone regeneration [24,30,31,40]. Our data also do not concur with the reported inhibitory effects of adenosine analogues, acting via A 1 or A 2A receptors, on the differentiation of rodent osteoblast-like cells [41] or human osteoblasts [40].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The work presented here showed no effects of adenosine, 2-chloroadenosine, GR79236 or BAY606583 on calvarialderived osteoblasts; this is in broad agreement with previous studies which showed exogenous adenosine had no effect on cultured rat osteoblasts [11,29]. However, our results are at variance with several studies which found that adenosine or adenosine analogues, acting via the A 2A or A 2B receptors, stimulate the differentiation and function of human and rodent bone marrow osteoblasts and promote bone regeneration [24,30,31,40]. Our data also do not concur with the reported inhibitory effects of adenosine analogues, acting via A 1 or A 2A receptors, on the differentiation of rodent osteoblast-like cells [41] or human osteoblasts [40].…”
Section: Discussionsupporting
confidence: 92%
“…However, A 1 and A 2B receptor knockout mice are reported to display increases in the trabecular and/or cortical bone [23,30], whilst A 2A receptor knockout mice have decreased cortical and trabecular bone [33]. At Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, another study indicated that adenosine, acting via the A2B receptor, may increase the osteogenic differentiation of rat long bone mesenchymal stem cells (Gharibi et al, 2011). Furthermore, a synthetic A2B receptor agonist has been shown to increase bone formation, and osteoblasts from A2B receptor knockout mice display reduced activity in vitro (Carroll et al, 2012). Recently, it was reported that the adenosine generated by ecto-5'-nucleotidase (CD-73) was important in promoting osteoblast differentiation (Takedachi et al, 2012).…”
Section: P1 Receptor Signalling and Osteoblastsmentioning
confidence: 99%
“…Both of the papers use an in vivo KO mouse approach-(1) Takedachi et al [14] use a model where adenosine production is compromised and (2) Carroll et al [15] use a model where the A2B AR, previously identified to be important for osteoblast differentiation, is missing. It is interesting to note that Takedachi et al highlight that (1) CD73 expression is regulated by Wntbcatenin signalling [16], a known critical pathway in bone metabolism and (2) the hypoxia inducible factor-1a (HIF1a), a transcription factor reported to be important for bone regeneration and skeletal development also regulates CD73 expression.…”
Section: Commentarymentioning
confidence: 99%